Selling to an agency - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Selling to a crop buying agency is another marketing strategy that small-scale farmers may chose to adopt. This interview features a Zambian co-operative that sells its export vegetables (Mange Tout, Fine Beans, Babycorn)to an agency, for which it has to fulfil very strict production standards. It also sells vegetables (tomatoes, carrots, onions), to local buyers, competing with cheap imports by inviting buyers to the farm.